KELAYAKAN USAHA NELAYAN PANCING TUNA DI JAZIRAH LEIHITU - Lolita Tuhumena; Agustinus Tupamahu; Leopold Arthur Tomasila (Universitas Pattimura, 2020)
Tuna fishing activities using troll line tool is an optional activity that has been occupied by the community in Peninsula Leihitu. The activities have been occupied since hereditary and their life depends on fishery resources. In reality, most of coastal communities are still living below the poverty line. The aim of this research is (1) to analyze the thecnical, economic, social and institutional condition of tuna fishing fisherman, (2) to analyze the income level and the feasibility of fishing business in Ureng, Assilulu and Larike (Dusun Lai) of Central Maluku Regency. The used research methods include statistical descriptive analysis, income analysis, investment criteria analysis. The study was conducted for 6 months from October 2017-March 2018. Data required in the study consists of primary data and secondary data. Sampling is done purposively of 55 fishermen (30%) from total population of tuna fishermen line which is still active doing fishing activity. Based on the results of research income analysis of this business make a profit. The result of analysis calculation of investment criteria obtained value NPV>1, Net B/C>1 and IRR> discount rate, indicating that tuna business in Ureng, Assilulu and larike (Dusun Lai) is a well run.